2013
DOI: 10.1080/21577323.2012.714839
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Design and Placement of Work-Zone Warning Signs on Driver Speed Compliance: A Simulator-Based Study

Abstract: OCCUPATIONAL APPLICATIONS In this work, simulated driving was used to test how characteristics of dynamic message signs impact driver behavior when entering designated work zones. Driver compliance with posted speed limits was measured in response to signs that differed in terms of placement distance and type of sign design. Signs should be placed farther ahead of the work zone to enhance speed compliance. Such compliance can also be enhanced by using concise sign content. TECHNICAL ABSTRACT Background and Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For school zones, these factors include types of school zones (school zone compared to playground) (Tay, 2009;Kattan et al, 2011), number of lanes (2-lane roads vs. 4-lane roads) (Tay, 2009;Kattan et al, 2011), presence of children (Kattan et al, 2011), length of the speed zone (Strawderman et al, 2013;Kattan et al, 2011), approach speed (Saibel et al, 1999;McCoy and Heimann, 1990), types of schools (elementary school vs. high school) (Day, 2007), presence of fencing (Tay, 2009;Kattan et al, 2011) etc. Kattan, et al, (2011) found that in the situation when there is 2-lane roads, roads with fencing, traffic control devices and the presence of speed display device or children, and zones that were longer, drivers' mean speeds were lower, and the rate of compliance was higher.…”
Section: Driver Speed Compliancementioning
confidence: 99%
“…For school zones, these factors include types of school zones (school zone compared to playground) (Tay, 2009;Kattan et al, 2011), number of lanes (2-lane roads vs. 4-lane roads) (Tay, 2009;Kattan et al, 2011), presence of children (Kattan et al, 2011), length of the speed zone (Strawderman et al, 2013;Kattan et al, 2011), approach speed (Saibel et al, 1999;McCoy and Heimann, 1990), types of schools (elementary school vs. high school) (Day, 2007), presence of fencing (Tay, 2009;Kattan et al, 2011) etc. Kattan, et al, (2011) found that in the situation when there is 2-lane roads, roads with fencing, traffic control devices and the presence of speed display device or children, and zones that were longer, drivers' mean speeds were lower, and the rate of compliance was higher.…”
Section: Driver Speed Compliancementioning
confidence: 99%
“…Moreover, DMS control strategies affect the behavior of drivers in advance through compliance with speed reductions. For example, Strawderman et al [9] investigated the impacts of DMS control strategies and sign placement on the behaviors of drivers approaching work zones by testing four DMS strategies and three placement distances (1,000, 1,500, and 2,000 feet) using a driving simulator; the results indicated that the resulting reduction in the driving speed was significantly impacted by the strategy employed. However, recent studies have also explored the misapplications of DMSs in work zones and revealed that DMSs can often contribute to driver confusion and anxiety regarding their appropriate path.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The speed may have been influenced by the speed limit signs (limit speed = 80 km/h) that were set at the start of the control area, and drivers likely increased their speed when they noticed that their speed was lower than the posted speed limit. Notably, the speed of the vehicle approaching the start of a work zone impacts the safety immediately; consequently, several studies have investigated the work zone safety based on the approaching speed [9]. Strategy 2 had the maximum approaching speed (82 km/h > 80 km/h), and strategy 3 had the lowest (75 km/h).…”
Section: Effects Of the Control Strategies On The Drivers' Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that PVMS placed in advance of work zones is an effective tool in reducing driver speeds. Strawderman et al [10] investigated the distance at which the VMS can be placed before the work zone. The study showed that VMS was effective in decreasing the speed of a vehicle when it was placed 500 m away from the work zone, when drivers had enough time to reduce their speeds gradually while approaching the work zone.…”
Section: Literature Reviewmentioning
confidence: 99%